Forms of the Religious Inclusion of Science into Culture - Ruzgienė, Valentina (Problemos, 1984)
Two forms of inclusion of science into culture are discussed, namely, the employment of science by church and the inconceived synthesis of science with elements of religion in atheist systems. One can see how in Catholic Church such traditional features as institutionalism, dogmatism of principles, sacredness of authority, monism which unify the concept and make it unique and, finally, monologicality as a form and style of addressing the audience lose their lucidity. To some extent this occurs under the influence of science to which Christians must address themselves. At the same time in some atheist systems gnoseological distortion of science and scientific character occurs because of dogmatic, authoritative attitude to knowledge, scientist, philosopher, ideologist.